2016
DOI: 10.1097/sla.0000000000001302
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival After Primary Tumor Surgery in Metastatic Breast Cancer

Abstract: The present study-the first population-based analysis using propensity score methods-provides evidence of a favorable impact of primary tumor surgery on mortality in metastatic breast cancer patients. Most importantly, the benefit of primary tumor surgery increased over time from 1998 to 2009. Although the final results of ongoing randomized studies are awaited, currently available evidence should be discussed with metastatic breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 42 publications
8
54
0
Order By: Relevance
“…Our findings are consistent with many previously published population‐based and single‐institution retrospective studies,( reporting improved outcome with primary tumor resection in stage IV breast cancer at presentation. Retrospective studies including our study are associated with several limitations, such as inability to control for selection bias.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with many previously published population‐based and single‐institution retrospective studies,( reporting improved outcome with primary tumor resection in stage IV breast cancer at presentation. Retrospective studies including our study are associated with several limitations, such as inability to control for selection bias.…”
Section: Discussionsupporting
confidence: 92%
“…Our study results indicating benefit from PTR are consistent with previous population‐based studies, but included a broader time period (until 2011), and also highlights temporal trend of overall decrease in PTR for metastatic breast cancer along with improved survival toward later decades, attributed most likely to better imaging, patient selection and improvement in systemic therapy, and surgical techniques . Retrospective studies are overwhelmingly suggesting subset of metastatic breast cancer will benefit from surgical resection of primary tumor.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our research, several analysis have also reported that primary tumour surgery has a favourable prognostic impact in stage IV breast cancer patients171833. We used a Cox proportional regression model by adjusting for all the prognostic factors and demonstrated an obvious benefit of primary tumour removal.…”
Section: Discussionsupporting
confidence: 69%
“…Retrospective observational study is prior than prospective randomized trials because it has no selection bias by entering good performance and small tumor patients possibly benefitting most from primary surgery in such trials [32]. This retrospective study used SEER registry data.…”
Section: Discussionmentioning
confidence: 99%